سبل تفعيل برامج اعداد المعلمين بكليات التربية السورية من وجهة نظر أعضاء الهيئة التعليمية - ناصر, محمد جودت; طرابلسية, شيراز محمد عشير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
ُيظهر البحث أنه في ظل الظروف الجديدة ومستجدات العصر الحالية أصبح التطوير الجامعي وخاصة تطوير كليات التربية ضرورة ملحة. انطلاقا من ذلك تمّ إجراء دراسة انفردت بها كلية التربية في جامعة دمشق، توضحت من خلالها مظاهر الأزمة التي تمر بها هذه الكلية، مستندةً بذلك إلى مبررات ومحددات تطويرها ومستويات الجودة والتمٌَيز فيها. وفي النهاية توصلت الدراسة الى ضرورة تدعيم الصلة بين كليات التربية ومدارس التعليم العام من جهة، والتشبيك مع المؤسسات التربوية والاجتماعية والثقافية من جهة أخرى، واختٌتمتَ بمجموعة من التوصيات يمكن أن تسهم بتطوير كليات التربية عموما. The present research shows that within the new context and recent developments in higher education, university upgrading, especially in education faculties, has become an urgent necessity. An exclusive study in the Faculty of Education at the University of Damascus has clearly shown the different aspecs of the crises in the faculty, based on the justifications and determinants of their development, as well as their levels of quality and excellence. Finally, the research emphsises the need for strengthening linkages between faculties of education and public universities on one hand, and networking with educational, social and cultural institutions on the other hand. At the end it providessome recommendations that could contribute to improving the level of the faculties of education in general.